2002
DOI: 10.1093/jn/132.6.1319
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Dietary Phytoestrogens by Dutch Women

Abstract: Higher consumption of phytoestrogens might be protective against certain chronic diseases. Accurate quantification of habitual phytoestrogen intake is important for assessing associations between phytoestrogens and risk for certain diseases. The aim of this study was to estimate dietary intake of phytoestrogens in Dutch middle-aged and elderly women and to describe their main sources. Women were recruited between 1993 and 1997 and aged 50-69 y at enrollment (Prospect-EPIC; n = 17,357). A detailed food frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
93
7
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 69 publications
9
93
7
2
Order By: Relevance
“…Non-MED countries had slightly higher, though still relatively low levels of estimated isoflavone intake (0.76 mg/day), which is comparable to other reported data (from 0.23 to 0.96 mg/day). 4,34,35,43 These low intakes are consistent with estimates for other Western countries such as Canada (0.31 mg/day) 20 and US (around 1.1 mg/day). 37,44 In the UK general population, the isoflavone intake was also higher (2.34 mg/day) compared with other European countries because of the addition of soy flour to regular flour used in baking.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Non-MED countries had slightly higher, though still relatively low levels of estimated isoflavone intake (0.76 mg/day), which is comparable to other reported data (from 0.23 to 0.96 mg/day). 4,34,35,43 These low intakes are consistent with estimates for other Western countries such as Canada (0.31 mg/day) 20 and US (around 1.1 mg/day). 37,44 In the UK general population, the isoflavone intake was also higher (2.34 mg/day) compared with other European countries because of the addition of soy flour to regular flour used in baking.…”
Section: Discussionsupporting
confidence: 86%
“…The highest intake of phytoestrogen was in the UK healthconscious group (22.41 mg/day). MED countries had the lowest phytoestrogen intake (1.52 mg/day), followed by non-MED countries (2.11 mg/day) and UK general population (4.04 mg/day), showing similar results as those published in individual European countries, such as The Netherlands, 34 Sweden 35,36 and UK 4 (0.58-3.17 mg/day), and in the US (1.11-2.02 mg/day) 37 or Canada (1.17 mg/day). 20 The UK health-conscious cohort is made up predominantly of lacto-ovo vegetarians and vegans; therefore they consume more plant foods, especially soy products that are the most abundant food sources of phytoestrogens.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, not all epidemiological and surveillance studies have biological samples available, and many studies have relied on reports of food intake and associated phytoestrogen databases to assess phytoestrogen exposure in relation to disease risk (28)(29)(30)(31)(32). Previous food analyses have mainly been limited to isoflavones in fruit, vegetables, nuts, and seeds, and there is little data available for lignans and animal foods (33-36) (37).…”
Section: Introductionmentioning
confidence: 99%
“…They act as a weak estrogen, and their antiestrogenic properties have been observed as well -dependent on the hormonal environment of the organism (Wang et al, 1996;Fritsche and Effects of genistein and genistin on in vitro maturation of pig oocytes Steinhart, 1999;Rosselli et al, 2000). In human beings the intake of higher amounts of phytoestrogens in foods is usually connected with positive effects on health concerning some chronic diseases like cancer, osteoporosis or cardiovascular diseases (Boker et al, 2002;Kayisli et al, 2002;Moravcová and Kleinová, 2002). Nevertheless, not all studies have confirmed such a positive concept until now (e.g.…”
mentioning
confidence: 99%